An Analysis Students’ Motivation in Reading Procedure Text at the First Grade of SMA Ekasakti - Elda Martha Suri (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2017)
This research discussed about students motivation in reading procedure text at the first grade of SMA Ekasakti University. This research is important to conducted because with analysis students motivasion can preapared steps to increasing students reading skill.t The technique of analyzing the data the researcher was descriptive qualitative. Questionnaire was used to collect the data. The finding showed that there was any significant analysis students’ motivation. It could be showed that from 21 students in reading procedure text, there were10 students (60-79%) in good, 4 students (50-59%) and in poor,and 7 students (0-49) very poor category.